2019
DOI: 10.3892/etm.2019.7585
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum transforming growth factor β1, interleukin‑6 and neonatal respiratory distress syndrome

Abstract: Trend and correlation of transforming growth factor β1 (TGF-β1) and interleukin-6 (IL-6) in serum of children with neonatal respiratory distress syndrome (NRDS) were investigated. A total of 75 NRDS children born in the Xiangyang Central Hospital from July 2015 to August 2017 were analyzed retrospectively. A total of 45 NRDS premature infants who received pulmonary surfactant (PS) within 12 h after birth were treated as PS group, 30 who did not receive PS treatment as non-PS group, and 32 premature infants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…NRDS arises in approximately 7% of all neonates and is a leading cause of death in preterm neonates (<37 gestation weeks). 18,19 Thus, close imaging monitoring and instant treatment of NRDS is urgently needed. Currently, a variety of imaging techniques and modalities have been introduced, including chest radiology, computed tomography (CT), fluoroscopy, MR imaging, nuclear medicine, and ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NRDS arises in approximately 7% of all neonates and is a leading cause of death in preterm neonates (<37 gestation weeks). 18,19 Thus, close imaging monitoring and instant treatment of NRDS is urgently needed. Currently, a variety of imaging techniques and modalities have been introduced, including chest radiology, computed tomography (CT), fluoroscopy, MR imaging, nuclear medicine, and ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…NRDS arises in approximately 7% of all neonates and is a leading cause of death in preterm neonates (<37 gestation weeks) 18,19 . Thus, close imaging monitoring and instant treatment of NRDS is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor β1 (TGF-β1) is a cytokine, which has the responsibility for regulating and differentiating different cell lines [20,21]. These studies have marked the role of TGF-β1 in development of various acute and chronic lung injuries and concluded that this factor can be used as a diagnostic and prognostic one [22]. The same role has been considered for interleukin-6, which is a glycoprotein secreted mostly from T cells and mononuclear macrophages causing inflammatory reactions [23,24].…”
Section: Laboratory Testsmentioning
confidence: 99%